1978
DOI: 10.5962/bhl.title.69039
|View full text |Cite
|
Sign up to set email alerts
|

Predicting slash depth for fire modeling /

Abstract: after 12 years of pure and applied research and systems analysis both in private industry and at the nonprofit Institute for Defense Analyses. JAMES K. BROWN received his bachelor's degree from the University of Minnesota in 1960, his master's from Yale University in 1961, and his Ph.D. from the University of Michigan in 1968, all in forestry. From 1961 to 1965 he did research on field measurement of fuel properties and fire-danger rating systems while with the Lake States Forest Experiment Station. In 1965, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Dead fuel is often more flammable than live foliage due to a lower heat of ignition and processes that control moisture absorption and retention [107,131]. Higher wind speeds are required to carry crown fire through the epidemic stands because dead foliage falls relatively quickly from bark beetle-attacked spruce [107,132]. Seasonal drying and prolonged drought may also cause both live and dead fuels to become even more flammable [133].…”
Section: Crown Fire Behaviormentioning
confidence: 99%
“…Dead fuel is often more flammable than live foliage due to a lower heat of ignition and processes that control moisture absorption and retention [107,131]. Higher wind speeds are required to carry crown fire through the epidemic stands because dead foliage falls relatively quickly from bark beetle-attacked spruce [107,132]. Seasonal drying and prolonged drought may also cause both live and dead fuels to become even more flammable [133].…”
Section: Crown Fire Behaviormentioning
confidence: 99%
“…The depth of the fuel bed determined as an output of the planar intercept method (Brown 1974) is called the "average high particle depth." Albini and Brown (1978) showed that for logging slash fuel beds, the Fuel Bed Depth is approximately 63.3 percent of the average high particle depth. For the special case fuel model, palmetto-gallberry (P-G), Fuel Bed Depth is calculated as 2/3 of the P-G Height of Understory variable entered on the worksheet.…”
Section: Second Fuel Modelmentioning
confidence: 99%
“…Since the late 1970s, live and dead woody and herbaceous fuel loading has been calculated through equations that use constant bulk densities over a management unit [22] or estimated using ocular estimates (e.g., [14,23]). They assume a constant fuel bulk density regardless of fuel height, which results in a monotonic increase in fuel load with depth [22,24]. Hence, fuels have historically been viewed through a coarse lens, despite the importance of fine scale fuel variation to fire ecology [17,25,26].…”
Section: Introductionmentioning
confidence: 99%